PSYCHOLOGICAL AND PEDAGOGICAL CONDITIONS OF CIVIC EDUCATION OF JUNIOR SCHOOLCHILDREN IN SOCIO-CULTURAL CONDITIONS OF CRIMEA (Pedagogy of Higher and Secondary Education, 2022)
The article deals with psychologic-pedagogical conditions of civil education of juniors in social cultural conditions of Crimea, showed peculiarities of social cultural environment of Crimean peninsula.
Keywords: civil education; social cultural conditions; civil society